Extracellular Vesicles from Adipose Tissue—A Potential Role in Obesity and Type 2 Diabetes? - Gao, Xuan; Salomon, Carlos; Freeman, Dilys J. (Frontiers in Endocrinology, 2017)
Adipose tissue plays a key role in the development of insulin resistance and its pathological sequelae such as type 2 diabetes and non-alcoholic fatty liver disease. Dysfunction in the adipose tissue response to storing excess fatty acids as triglyceride can lead to adipose tissue inflammation and spillover of fatty acids from this tissue and accumulation of fatty acids as lipid droplets in ectopic sites such as liver and muscle. Extracellular vesicles (EV) are released from adipocytes and have been proposed to be involved in adipocyte/macrophage crosstalk and to affect insulin signalling and TGFβ expression in liver cells leading to metabolic disease. Furthermore EV produced by adipose tissue-derived mesenchymal stem cells (ADSC) can promote angiogenesis and cancer cell migration and have neuroprotective and neuroregenerative properties. ADSC EV have therapeutic potential in vascular and neurodegenerative disease and may also be used to target specific functional miRNAs to cells. Obesity is associated with an increase in adipose-derived EV which may be related to the metabolic complications of obesity. This review aims to discuss EV produced by adipose tissue and their potential impact on metabolic diseases associated with obesity.